Trade Competition, Technology and Labour Reallocation - Selva B. Baziki; Rita Ginja; Teodora Borota Milicevic (Institute for the Study of Labor (IZA), 2016)
This paper provides new evidence on the reallocation of workers across firms and industries with different technologies in response to increased import competition from developing countries. Using employer-employee matched data for the Swedish manufacturing sector, we find increased assortative matching of workers in ICT (information and communication technologies) intensive industries, that is, high(low)-wage workers sort into high(low)-wage firms. Industries with low ICT intensity do not exhibit these sorting patterns. A labour market matching model explains the increased assortative matching in ICT intensive industries in response to stronger import competition through an increase in the relative demand for qualified workers.
Keywords: F16; J63; O33; 330; wage inequality; employment dynamics; assortative matching; import competition; technological change